Adsorptive Removal of Iron Using SiO2 Nanoparticles Extracted from Rice Husk Ash. (2nd June 2019) - Nguyen, Tan Tai; Ma, Hoa Thai; Avti, Pramod; Bashir, Mohammed J. K.; Ng, Choon Aun; Wong, Ling Yong; Jun, Hieng Kiat; Ngo, Quang Minh; Tran, Ngoc Quyen
Abstract : In this work, SiO2 nanoparticles were prepared by the sol-gel method after sodium silicate was extracted from rice husk ash (RHA) under various experimental conditions such as types of acids, NaOH concentration, dissolved time, and temperature and used for removal of Fe 2+ ions from aqueous solutions. The extracted SiO2 was morphologically and chemically characterized and showed a surface area of 78 m 2 /g and uniform pores of 2.71 nm, offering high adsorption capacity for Fe 2+ ions. The influence of pH, contact time, and amount of adsorbent was studied in order to establish the best conditions for the Fe 2+ adsorption and removal. Furthermore, the adsorption data were fitted with an exponential shape curve for all the three variable parameters that affect the adsorption process. The best results were obtained for pH 5, 20 min contact time, and 0.5 g adsorbent dose. The loading adsorption capacity was 9 mg of Fe 2+ ions/g SiO2 in the concentration range 0.1–1.0 mgL −1 . In addition, the synthesized SiO2 with the size of around 50 nm can be used for specific heavy metal removal and drug delivery, after modification of the SiO2 surface with various functional groups.